Determination of Serum Copper Levels Effect on Learning Ability Among Apparently Healthy Schooling Adolescents Recruited from Sokoto, Nigeria - Imam, Aminu Umar; Sarkingobir, Yusuf (Darul Yasin Al Sys, 2024)
Copper is vital for human biological system especially for learning functions. The objective of this paper was to determine the effects of serum copper on learning ability among adolescents in Sokoto, Nigeria. Therewith, serum copper concentrations of the 230 recruited adolescents’ in-school from Sokoto, Nigeria were analyzed using the atomic absorption spectroscopy method, and reagents of analytical grade. The investigation of effect of copper concentration on learning potential was done in a quasi-experimental format. The findings (p<0.05) of serum copper concentration revealed mean serum copper in healthy subjects was 211(91.74%); serum copper deficient subjects were 19(8.26%). The low copper concentration observed based on age shows, 13(5.6%) of 14-16 years; and 6(2.6%) of 16-18 years. Observation of copper level in relation to learning potential show a mean of 62.28 in normal participants, and 36.92 in low copper participants. There is need for utmost diverse nutritional intervention on zinc consumption. There are still some adolescents that have low copper level in the state, and it may affect their learning and entire learning. Thus, it is important to provide better nutrition through using disparate intervention methods to bail the situation.